Pluralism: the origins of a theory for crisis times - Mussi, Daniela (Universidade Estadual Paulista / UNESP, 2013)
This article reviews the theory of the rise of “interestgroup liberalism” in political science as an attempt to solve a paradigmatic crisis from the early twentieth century in the United States. This under the historical context of emergency of management and statism as central challenges on politics. This, by the criticism of the concept of sovereignty and proponent of the concept of interest groups as explanatory basis of the policy, sought to compose a new “public philosophy” and a scientific methodology for the study of politics. Finally, the paper presents elements for a general critique of pluralism, pointing out the challenges for a realistic and critical political science, capable of restoring the centrality of political parties and the public interest.